Oral challenge of turkey poults with Mycoplasma iowae - M. Shah, Majid; Rosendal, S. (American Association of Avian Pathologists, 1986)
Day-old poults were inoculated orally each day for 7 days with 0.2 ml of Mycoplasma iowae, strain D112, 10(8) colony-forming units/ml. Cloacal swabs were taken from each poult during the inoculation period and at selected intervals until 21 days after the last inoculation. Most poults shed mycoplasmas persistently after inoculation. Cloacal swabs from eight out of ten poults were positive at 21 days after the last inoculation. Feces of poults in the infected group were normal, and there was no significant rise in cloacal temperature. At necropsy, mycoplasmas were recovered from tissues of the respiratory tract, gastrointestinal tract, spleen, and kidney. In the gastrointestinal tract, the most frequent recoveries were from the wall of the distal portion of the small intestine, cecum, and large intestine. Recovery of M. iowae from these organs and tissues indicated infection following oral challenge